2023
DOI: 10.1177/17562872231158072
|View full text |Cite
|
Sign up to set email alerts
|

RIRS with disposable or reusable scopes: does it make a difference? Results from the multicenter FLEXOR study

Abstract: Introduction: With several single-use ureteroscopes now available, our aim was to analyze and compare data obtained globally from high-volume centers using both disposable and reusable flexible ureteroscopes and see if indeed in real-world practice either scope has a distinct advantage. Methods: Retrospective analysis was performed on the FLEXOR registry, which was created as a TOWER group (Team of Worldwide Endourological Researchers, research wing of the Endourological Society) endeavor. Patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Ozimek et al [20] determined the average cost of ru-fURS to be €503.26 per case and concluded that su-fURS would be more expensive in high volume centers, but that they may be cost effective in certain cases involving high risk of scope damage, such as multiple or large stones in the lower pole of recurrent stone formers and a steep infundibular pelvic angle. Gauhar et al [21] conducted a retrospective analysis of the FLEXOR registry in order to examine data collected globally from high-volume centers employing both su- and ru-fURS. According to the results, urologists choose su-fURS for bigger, lower pole, and harder stones, and it does indeed aid in improving the single-stage SFR if used correctly.…”
Section: When Single Use Scopes Should Be Used To Be Actually Cost Ef...mentioning
confidence: 99%
“…Ozimek et al [20] determined the average cost of ru-fURS to be €503.26 per case and concluded that su-fURS would be more expensive in high volume centers, but that they may be cost effective in certain cases involving high risk of scope damage, such as multiple or large stones in the lower pole of recurrent stone formers and a steep infundibular pelvic angle. Gauhar et al [21] conducted a retrospective analysis of the FLEXOR registry in order to examine data collected globally from high-volume centers employing both su- and ru-fURS. According to the results, urologists choose su-fURS for bigger, lower pole, and harder stones, and it does indeed aid in improving the single-stage SFR if used correctly.…”
Section: When Single Use Scopes Should Be Used To Be Actually Cost Ef...mentioning
confidence: 99%
“…Many studies focus on several variables like demographic factors, 1 stone parameters, 2 and intraoperative technical steps and technology used 3 to predict stone-free rate (SFR) and outcomes of retrograde intrarenal surgery (RIRS) in adults and children alike. Similarly, preoperative computerized tomography (CT) imaging for endourological intervention is ideal for kidney stones and to estimate stone parameters like Hounsfield units (HU), 4 and its ability to influence decision-making for RIRS has been well documented.…”
Section: Introductionmentioning
confidence: 99%